Discretion in bank loan loss allowance, risk taking and earnings management. (8th March 2016) - Jin, Justin; Kanagaretnam, Kiridaran; Lobo, Gerald J.
Abstract: We study whether banks use the allowance for loan losses (ALL) for efficiency or for opportunistic reasons. We find that banks that had higher abnormal ALL during the period prior to the 2007–2009 crisis engaged in less risk taking during the pre‐crisis period and had a lower probability of failure during the crisis period. In testing earnings management to meet or beat earnings benchmarks, we find that abnormal ALL is unrelated to next period's loss avoidance and just meeting or beating the prior year's earnings. Our results suggest that banks use ALL for efficiency and not for opportunistic purposes.